2002
DOI: 10.1007/s005340200067
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A 68-year-old man complaining of jaundice was admitted to our hospital in October 1996. Radiological imaging studies, including dynamic computed tomography, endoscopic retrograde cholangiography, and angiography, were highly suggestive of pancreatic head cancer, and laparotomy was performed on October 25, 1996. On gross examination, the pancreas appeared firm, as in chronic pancreatitis, with a mass lesion in the pancreatic head measuring 35 x 35 x 25 mm. A pylorus-preserving pancreatoduodenectomy was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Preoperative or even intraoperative diagnosis can be problematic, particularly in patients for whom there are no clinical grounds to suspect LSP. It has been suggested that surgical resection may be an effective treatment for LSP especially when immunological tests are normal or when malignancy is highly suspected (this may be the only option to exclude malignancy) [18]. However, surrounding inflammation can make surgical resection hazardous, so a trial of steroids is worthwhile if a confident diagnosis can be made without laparotomy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative or even intraoperative diagnosis can be problematic, particularly in patients for whom there are no clinical grounds to suspect LSP. It has been suggested that surgical resection may be an effective treatment for LSP especially when immunological tests are normal or when malignancy is highly suspected (this may be the only option to exclude malignancy) [18]. However, surrounding inflammation can make surgical resection hazardous, so a trial of steroids is worthwhile if a confident diagnosis can be made without laparotomy [18].…”
Section: Discussionmentioning
confidence: 99%